RESEARCH TRENDS ON LISTENING ASSESSMENTS - Ab Rahman, Hazlinah; Md Idrus, Norazah; Abdul Ghani, Noor Amili (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
The growing importance of listening skills in education and language acquisition has led to increasing scholarly attention on listening assessment. However, despite this interest, there is a limited amount of bibliometric research that maps the global research landscape, identifies key contributors, and analyzes thematic trends in this domain. This study addresses this gap by conducting a comprehensive bibliometric analysis of the literature on "listening assessment." Using Scopus as the primary database, an advanced search with the keywords "listening" and "assessment" retrieved 884 relevant documents. The data were first analyzed using Scopus Analyzer to extract statistical insights related to publication trends, prolific authors, top journals, and influential countries. OpenRefine was then employed to clean and harmonize metadata, ensuring consistency in author names, institutions, and keywords. VOSviewer software was utilized to generate network visualizations, including co-authorship networks, keyword co-occurrence maps, and country collaboration patterns. The analysis revealed a steady growth in publications over the last two decades, with the United States, United Kingdom, and China emerging as leading contributors. Thematic clustering of keywords indicated strong research interest in areas such as "language testing," "listening comprehension," "assessment tools," and "language proficiency." Co-authorship and country collaboration maps showed increasing international cooperation, particularly among English-speaking and Asian countries. These findings provide valuable insights into the development and focus of research on listening assessment, highlighting dominant themes and underexplored areas. This study not only contributes to the academic understanding of how listening assessment is evolving but also offers direction for future research and policy development in educational assessment and language learning.